Organizational Citizenship Behaviors and Sales Unit Effectiveness - Posdakoff, Philip M.; Mackenzie, Scott B. (Journal of Marketing Research, 1994)
Organizational citizenship behaviors (OCBs) are defined as discretionary, extra-role behaviors on the part of a salesperson that have been shown to influence managers’ evaluations of performance. It has been suggested that one reason managers value OCBs is that they believe OCBs contribute to organizational success. The authors’ purpose is to investigate the impact of OCBs on objective unit performance and compare this effect with the impact that OCBs have on managerial evaluations. First, the impact of OCBs on overall performance evaluations is examined. Second, the aggregate effects of unit-level OCBs on agency performance are examined using objective performance data for 116 agencies in a major insurance company. The results show that OCBs make an important contribution to overall agency performance; however, some citizenship behaviors appear to help and others hinder agency performance. Finally, a comparison of the results of the two studies suggests that managers tend to overvalue some citizenship behaviors and undervalue others.